2010
DOI: 10.1029/2009gb003484
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration and its potential in agricultural soils of China

Abstract: [1] Agricultural soils hold potential for the expansion of carbon sequestration. With this in mind, we investigated changes in the soil organic carbon (SOC) on the basis of an analysis of data sets extracted from 146 publications and further projected the SOC sequestration potential in China's cropland. Our results suggest that a significant increase in the SOC occurred in east and north China, while a decrease appeared in northeast China. As a whole, the organic carbon density in the topsoil to 30 cm depth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
3
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 67 publications
2
89
3
3
Order By: Relevance
“…The soil C sequestration amounts in Scenarios I and II could respectively account for 2.43 % and 2.83 % of the C emissions from fuel use in China in 2010 (2.18 Pg C, IEA 2011). Soil C sequestration following adoption of SI in our results was slightly higher than in other reports from China (Table 4), because straw inputs were underestimated in previous reports (Yan et al 2007;Lu et al 2009;Sun et al 2010). Overall, soil C sequestration rates in China were higher than in Europe and the United States (Table 4), which might be attributable to the relatively larger initial soil organic C content in the other countries (Li et al 2003).…”
Section: Estimates Of Soil C Sequestration Under Si In Chinacontrasting
confidence: 55%
“…The soil C sequestration amounts in Scenarios I and II could respectively account for 2.43 % and 2.83 % of the C emissions from fuel use in China in 2010 (2.18 Pg C, IEA 2011). Soil C sequestration following adoption of SI in our results was slightly higher than in other reports from China (Table 4), because straw inputs were underestimated in previous reports (Yan et al 2007;Lu et al 2009;Sun et al 2010). Overall, soil C sequestration rates in China were higher than in Europe and the United States (Table 4), which might be attributable to the relatively larger initial soil organic C content in the other countries (Li et al 2003).…”
Section: Estimates Of Soil C Sequestration Under Si In Chinacontrasting
confidence: 55%
“…With recurring application of mineral fertilizers matched to yield demands, soil fertility in China has improved in terms of soil nutrient status, but also soil organic carbon (SOC) since the 1980s (Sun et al, 2010). However, as several long-term field studies observed, excessive soil fertility, especially N fertilizer over-inputs in North China and East China caused nutrient imbalances, contributing to acidification, and decreasing C/N ratios (Darilek et al, 2009;Peng, 2011), but also resulting in a reduced yield response to continuously increasing chemical fertilizer use .…”
Section: Factors Influencing Regional Grain Yields Over the Last 20 Ymentioning
confidence: 99%
“…Furthermore, SOC losses from China's croplands have been widely reported (Huang and Sun, 2006;Qin et al, 2013;Sun et al, 2010). SOC stocks of agro-ecosystems may be increased by improving agronomic practices.…”
Section: Introductionmentioning
confidence: 99%